Analisis Perbuatan Melawan Hukum Terhadap Tanah Sita Eksekusi - Auliany, Nafisa; Adhan, Sepriyadi; Sumarja, F.X. (Indonesian Journal of Law and Justice, 2025)
This research aims to analyze whether the act is unlawful and legal protection for third parties in good faith. The method used is normative juridical, by examining the application of rules or norms in positive law and the type of research used in this research is descriptive research type with a problem approach using a case approach (legal case study). The legal materials used in this research are primary, secondary, and tertiary legal materials. The results of the research of Party B's actions can be categorized as unlawful acts in accordance with Article 1365 of the Civil Code which causes material and immaterial losses and and legal protection serves as a guarantee of legal certainty in buying and selling transactions in the event of a dispute can be resolved with a civil claim to the court.